Characterization of citrus bent leaf viroid (CBLVd) from citrus and it’s host range - Veloo, Navindrran (2017)
Citrus is a flowering plant and shrub that belongs to Rutaceae family which encompasses several variety of citrus such as orange, lemon, grape fruits, and limes. Citrus viroids cause devastating impact in the citrus industry by reducing yield and plant health. Geographically, citrus viroids are widely distributed and recently Citrus bent leaf viroid (CBLVd) RNA was detected in Malaysian citrus. Although citrus is an important industry in Malaysia, there is a lack of knowledge on the characterization and host range of CBLVd in Malaysia. The purpose of this study is to identify and characterize CBLVd from citrus and to determine its alternate hosts. Nucleic acid was extracted from the eight citrus plants using TELSP buffer. The extracted RNA was amplified by Reverse Transcription-Polymerase Chain Reaction (RT-PCR) using CBLVd specific primers. The RT-PCR products were separated using 2% agarose gel electrophoresis. RT-PCR products from positive samples were sequenced. Host range studies were conducted by using positive CBLVd samples from the citrus plants and inoculated into the alternate host through sap inoculation. The CBLVd variants characterized in this study showed high similarity with CBLVd isolate JP (AB006734.1) with a nucleotide length of 328nt. The viroid was found in Citrus microcarpa and Citrus maxima which exhibited virus and viroid like symptoms such vein yellowing, epinasty, midrib necrosis and stunted growth. The sap inoculated hosts tested with molecular assay for the presence of CBLVd but yielded negative result where CBLVd was not able to infect and develop symptoms in tomato, chilli, cucumber, and tobacco via sap inoculation.